On the Inversion of Lagrange-Dirichlet Theorem (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
We consider a Lagrangian differential system. The celebrated theorem of Lagrange-Dirichlet ensures that a stationary solution of this system is stable, provided that the corresponding critical point of the potential function is a proper {local} maximum.